The organisation of military violence in the 21st century. (July 2017) - Malešević, Siniša
In this article, I analyse the sociological foundations of military violence in the 21st century. The first part of the article engages critically with the three dominant contemporary approaches in the study of organised violence: (a) the decline of violence perspective, (b) the new wars theories and (c) the technological displacement approach. I argue that despite their obvious merits, these three perspectives do not provide adequate interpretation of recent social change. In particular, I contest their emphasis on the radical discontinuity in the character of the contemporary military violence when compared to the previous historical periods. Hence, to remedy this – in the second part of the article – I develop an alternative, a longue durée, sociological interpretation centred on the role of organisational, ideological and micro-interactional powers in the transformation of military violence. In contrast to the three dominant perspectives, I argue that the 21st-century organisation of military violence has changed but it still exhibits much more organisational continuity with the last two centuries than usually assumed. More specifically, my argument centres on the long-term impact of the three historical processes that have shaped the dynamics of military violence over long stretches of time: the cumulative bureaucratisation of coercion, centrifugal ideologisation and the envelopment of micro-solidarity.